Identifying the dimensions and components of ethical leadership competency of Educational Managers of Mashhad University of Medical Sciences (Descriptive-interpretive) - Hossein Abdollahi; Abbas Abbaspour; Leila Shoja Ghaleh Dokhtar; Asghar Minaee (Future of Medical Education Journal, 2022)
Background: Today, the discussion of ethical behavior and ethical values is a prerequisite for management, and all managers and employees of organizations must respect these principles. The purpose of this study was identifying the dimensions and components of ethical leadership in educational managers of Mashhad University of Medical Sciences with competency approachMethod: In this research, a qualitative method and the grounded theory approach were employed. The population of the study was educational managers and educational assistants of Mashhad University of Medical Sciences in the academic year 2019-2020 among whom sixteen were selected through theoretical sampling method. The data collection method was a semi-structured interview. The information obtained from the interview was analyzed using content analysis technique in data theory using MAXqda10 software.Results:  From the initial analysis of qualitative research data 513 codes were identified. In the next step, using axial coding, the identified codes were classified into 17 subcategories. Analysis of qualitative data showed that the component of ethical competence with sub-components (ethical knowledge, ethical attitude, and ethical skills) and technical competence with sub-components (technical knowledge, technical attitude, and technical skills) are the main components of ethical leadership in educational administrators of the University of Mashhad Medical Sciences.Conclusion: According to the dimensions of competency identified in the educational managers, it can be said when a training manager has the characteristic of ethical leadership he also knows what is morally right (ethical competence) and how to do it (Technical competence).